FC 014INFLUENCE OF GENETIC VARIATION IN SLC7A13/AGT1 IN HUMAN CYSTINURIA. (29th May 2021) - Schönauer, Ria; Seidel, Anna; Pöschla, Linda; Hantmann, Elena; Bekri, Soumeya; Knebelmann, Bertrand; Sayer, John; Ohgaki, Ryuichi; Halbritter, Jan
Abstract: Background and Aims: Cystinuria (CU) is an inherited renal disorder based on urinary wasting of dibasic amino acids, urinary precipitation, and consecutive cystine stone formation. It is caused by pathogenic variants in two distinct disease genes, SLC3A1 and SLC7A9, both of which encode subunits of a heterodimeric tubular amino acid transporter, rBAT/ SLC3A1 and BAT1/ SLC7A9, located at the apical membrane of proximal renal tubules. CU is marked by incomplete penetrance and substantial disease variability. Recently, a novel cystine transporter, consisting of the light chain AGT1/ SLC7A13 and its heterodimeric partner rBAT/SLC3A1 has been identified in the S3 segment of murine proximal tubules. In this study, we aim at evaluating the role of AGT1 in cystinuric patients with or without mutations in either SLC3A1 or SLC7A9, analyzing the role of AGT1/SLC7A13 as novel disease gene or genetic modifier in CU. Method: A multicenter European CU-cohort comprising 132 individuals was screened for pathogenic variants in SLC3A1, SLC7A9, and SLC7A13 using high-throughput multiplex PCR-based amplification and next-generation sequencing (MiSeq Illumina) followed by multiplex ligation-dependent probe amplification (MLPA) of SLC3A1 and SLC7A9 . For functional in vitro studies, epitope-tagged human and murine rBAT and AGT1 proteins were transiently expressed in different cell systems. Heterodimer complex formation was analyzed by co-immunoprecipitation and western blot studies and membrane trafficking was evaluated by immunofluorescence microscopy. Results: Genectic analysis of our CU-cohort did not reveal indiviuals with SLC7A13 variation only, however we found three patients harbouring heterozygous missense variants in addition to pathogenic or VUS variants in SLC3A1 or SLC7A9 . To evaluate their influence on the generation of functional cystine transporters in vitro, different cell models were transiently transfected with plasmids expressing wildtype or mutant proteins. In line with previous reports, co-expression of AGT1 and rBAT wildtype allowed efficient complex formation as AGT1-induced maturation of rBAT was detected by increased mature N-glycosylation, co-immunoprecipitation and membrane insertion. Whereas AGT1 patient variants p.Met452Thr ( SLC7A13 c.1355T>C) and p.Ile174Phe ( SLC7A13 c.520A>T) behaved comparable to wildtype AGT1, variants p.Asn45Lys ( SLC7A13 c.135C>G) and p.Leu270Phe ( SLC7A13 c.808C>T) led to clearly reduced glycosylation patterns and trafficking deficits of rBAT wildtype protein. Next, the mutual influence of pathogenic variation in both, AGT1 and rBAT, will unravel the consequences of patient-specific molecular interactions on the functional expression of cystine transporter complexes. Conclusion: Here, we report three CU-patients with variants in SLC7A13 combined with either SLC3A1 or SLC7A9. For two of these variants, in vitro functional analysis revealed pathogenic molecular mechanisms disturbing complex formation, maturation and trafficking of rBAT. We hypothesize that specific pathogenic variants in SLC7A13 interfere with efficient membrane localization of heterodimeric cystine transporters, which results in modulation of cystine transport in the S3 segment of proximal tubules in CU-patients.